Ki67 Index Changes and Tumor-Infiltrating Lymphocyte Levels Impact the Prognosis of Triple-Negative Breast Cancer Patients With Residual Disease After Neoadjuvant Chemotherapy - Wang, Yihua; Zong, Beige; Yu, Yu; Wang, Yu; Tang, Zhenrong; Chen, Rui; Huang, Man; Liu, Shengchun (Frontiers in Oncology, 2021)
Purpose The aim of this study was to assess the prognostic influence of Ki67 index changes in patients with primary triple-negative breast cancer (TNBC) treated with neoadjuvant chemotherapy (NAC), and to evaluate whether the combination of Ki67 index changes and residual disease (RD) tumor-infiltrating lymphocytes (TILs) provides additional prognostic information for this group. Materials and Methods Data from 109 patients with primary TNBC and RD after NAC were analyzed retrospectively. Ki67 changes and RD TIL levels were investigated for associations with recurrence-free survival (RFS) and overall survival (OS) using Kaplan–Meier and Cox analyses. Results Ki67 index decreased after NAC in 53 patients (48.6%) and high RD TIL levels (≥30%) were observed in 54 patients (49.5%). In multivariate Cox analyses, no Ki67 decrease status and low RD TIL levels were significantly associated with reduced RFS (hazard ratio (HR): 2.038, 95% confidence interval (CI): 1.135–3.658, P = 0.017; HR: 2.493, 95% CI: 1.335–4.653, P = 0.004), and OS (HR: 2.187, 95% CI: 1.173–4.077, P = 0.014; HR: 2.499, 95% CI: 1.285–4.858, P = 0.007), respectively. Notably, low RD TIL levels were significantly associated with reduced RFS (HR: 3.567, 95% CI: 1.475–8.624, P = 0.005) and reduced OS (HR: 3.873, 95% CI: 1.512–9.918, P = 0.005) in only the no Ki67 decrease group. The differences in 3-year RFS and OS between patients with no Ki67 decrease and low or high RD TIL levels were 24.4% vs 79.1% (P = 0.0001) and 33.1% vs 87.5% (P = 0.0001), respectively. Conclusion Ki67 index changes and RD TIL levels were associated with the prognosis of patients with primary TNBC with RD after NAC. RD TIL levels had greater prognostic significance in the no Ki67 decrease group.